Choosing a Budget Management System : The Case of Rwanda - Lienert, Ian (IMF Working Papers; Working Paper, 2004)
Rwanda is making important choices concerning budget processes. A program-oriented budget framework is now used. A new Constitution, adopted in May 2003, has made some important choices concerning the public management system, including the balance of power between the executive and the legislature. Further choices are being made in an organic budget law (under discussion). Compared with the inherited budget management model, the responsibility of spending agencies is likely to be enhanced. Choices have yet to be made on the nationwide government accounting system, the precise role of the Senate in budgeting, and the pace of effective political decentralization.